CHARACTERISTICS OF THE STATE OF IMPLEMENTATION OF FOREIGN EXPERIENCE IN TEACHING ACADEMIC DISCIPLINES AT THE MILITARY INSTITUTE OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV - Loishyn, Anatolii; Kucheriavyi, Andrii; Vanovska, Inna; Pyrogov, Kyrylo (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The study is dedicated to solving the problems of training domestic cadets and trainee officers, which arise due to the clash of paradigms of the officer's personality formation – as a performer (according to the traditions of the Soviet higher military school) and as a leader, in accordance with modern approaches to training military personnel in the leading countries of the world. In particular, we are talking about the problems of choosing a methodical system for conducting an educational session and the cadets' choice of methods of educational activity in view of activity, initiative, targeting the demonstration of critical thinking, that is, those characteristics of the training process that are determined by the state of implementation of foreign experience in teaching academic disciplines in a domestic institution of higher military education. The purpose of the article is to provide a description of the state of implementation of foreign experience in teaching academic disciplines at the Military Institute of Taras Shevchenko National University of Kyiv.M e t h o d s . The method of surveying chair heads was used; content analysis of scientific literature, which describes the conduct of educational activities at military academies of the leading countries of the world; the experimental method for substantiating the methodology of conducting training classes; quantitative and qualitative methods of scientific literature research; sociological observation of the results of the survey of respondents; systematic analysis of the practical problems of conducting various types of training classes and the course of implementation of methods of conducting training classes in accordance with the leading countries of the world; a systematic approach to the study of the conduct of educational classes in the military academies of the leading countries of the world; the experimental method of implementing the experience of the leading countries of the world in Military Institute.R e s u l t s . According to the results of the study, it was found that a certain part of scientific and pedagogical workers does not demonstrate that it relies on relevant foreign experience when teaching academic disciplines and, as a result, does not ensure the formation of the personality of an officer-leader. With this in mind, recommendations for conducting certain activities are given for such scientific and pedagogical workers.C o n c l u s I o n s . The future prospects of this research consist in the development of scientifically based recommendations regarding the content of work programs of educational disciplines and their other regulatory and methodological support, which is aimed at taking into account the foreign training experience of military personnel.
Keywords: methodical principles, cadets, classes, evaluation of classes, higher military school